From Campus to Corporate: Evaluating Industry Partnerships to Improve the BSOA Internship Program - Nollie Boy Dangli Jerson (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study evaluated industry partners and the implementation of the Bachelor of Science in Office Administration (BSOA) internship program from the perspective of interns, with the goal of identifying evidence-based priorities for program improvement. Methodology: An explanatory sequential mixed-method design was employed. Quantitative data were obtained from 70 BSOA interns from academic years 2022–2024 through total enumeration, followed by semi-structured interviews with 10 purposively selected interns using criterion-based maximum-variation purposive sampling. The survey instrument was adapted from a prior internship evaluation tool and contextualized to the BSOA practicum and CMO 104, series of 2017. Quantitative data were analyzed using frequency, percentage, and weighted mean, while qualitative interview data were coded thematically to explain the survey results. Main Findings: Interns rated collaboration and teamwork (4.33), regard for people (4.41), and work ethics (4.43) as excellent. Communication (4.18), decision-making and empowerment (4.06), and compliance with internship requirements (4.16) were rated very satisfactory. Time management (3.09) and low self-confidence (2.77) emerged as the most salient challenges, highlighting the need for clearer pre-deployment guidance, structured feedback, and continuous partner review. Novelty/Originality of this study: The study contributes a program-specific evaluation of internship quality in office administration education by integrating intern ratings of industry partnership quality, regulatory compliance, and encountered problems into a single improvement-oriented framework.